2015
DOI: 10.1038/npjpcrm.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Muslim communities learning about second-hand smoke: a pilot cluster randomised controlled trial and cost-effectiveness analysis

Abstract: Background:In the United Kingdom, men of Bangladeshi and Pakistani origin have higher smoking rates than the general population. This makes non-smokers in their households more vulnerable to second-hand smoke (SHS) exposure than the general population.Aims:The aim of this study was to investigate the feasibility of implementing and pilot testing the effectiveness and cost-effectiveness of a ‘Smoke-free Homes’ (SFH) intervention in Islamic religious settings to encourage families of Bangladeshi and Pakistani or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50]. If found to be effective in changing smoking behaviour in the home, this approach could be generalizable to other communities with similar male smoking norms where faith-based settings (i.e., churches, mosques, synagogues) play an integral part in their lives [48].…”
Section: Discussionmentioning
confidence: 99%
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50]. If found to be effective in changing smoking behaviour in the home, this approach could be generalizable to other communities with similar male smoking norms where faith-based settings (i.e., churches, mosques, synagogues) play an integral part in their lives [48].…”
Section: Discussionmentioning
confidence: 99%
“…The interventions have been co-produced with Muslim religious leaders and public health experts in Bangladesh, through an iterative process of adaptation of the SFH intervention developed as part of the MCLASS pilot trial (MR/J000248/1) [19] to the Bangladesh context. IAQ feedback, piloted in Scotland [24] and currently undergoing method development as part of a Medical Research Foundation (MRC) Public Health Intervention Development grant (MR/M026159/1) has also been adapted.…”
Section: Methodsmentioning
confidence: 99%
“…They will be asked to sign a written agreement to participate for their mosque and themselves. This approach is considered to be reasonable given the organisational structures within mosques based on the MCLASS pilot trial findings [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosques in the control arm did not receive the SFH intervention, but on completion of the trial they were offered the SFH educational package and a detailed guide on training RTs on its use. The detail on findings of the pilot trial in relation to recruitment, effect size, response rates and costs are reported elsewhere [ 31 ]. We present the summary of findings of the pilot trial in Box 1 .…”
Section: Introductionmentioning
confidence: 99%